ANALISIS LEASING PADA PERUSAHAAN PENYEDIA KAPAL PT. BAHANA UTAMA LINE DI SANGATTA - A, Febriadi Fajri (EKONOMIA, 2014)
The purpose of the study was to determine the calculation leasing by PT. Bahana Utama Line in Sangatta are in accordance with applicable accounting standards. The experiment was conducted for 3 months (April to June 2013) on PT. Bahana Utama Line, relating to Leasing your analysis on the provider Vessel Leasing. Activities undertaken research: The study of literature, field observations, interviews, documentation, data collection and analisis.Data that dikupulkan in the research include: a general overview of the company, organization structure and response data using analytical tools responden.Analisis calculations lease (leasing) by using the rate of interest the annuity formula. Based on the calculation of interest, principal payments and the calculation can be explained that the recording of the interest calculation performed by the accounting department leases 15% interest rate multiplied by the net lease debt principal payments are paid at the beginning of the year (Rp 780,000,000.00 – Rp 135,145,000.00 = Rp 644,855,000.00 x 15% = Rp 96,728,250.00) for the years 2011 and 2012 can be calculated (Rp 644,855,000.00 – Rp 38,416,750.00 x 15% = Rp 90,965,737.50 while the principal lease payments specified in the agreement which amounted to Rp 135,145,000.00 paid at the beginning of the year, and for the end of 2011 became principal payments of Rp 38,416,750.00 as principal payments each year reduced rate of Rp 96,728,250.00